Accuracy of 7-8-9 Rule: Neonatal Endotracheal Intubation - Sakhuja, P; Whyte, H; Finan, E (Journal of Nepal Paediatric Society, 2012)
DOI: http://dx.doi.org/10.3126/jnps.v32i1.5759 J. Nepal Paediatr. Soc. Vol.32(1) 2012 93